2020
DOI: 10.3389/fmicb.2020.01318
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evolutionary Analysis of a Novel H3N2 Influenza A Virus Glycosylation Motif in Southern China

Abstract: An influenza A (H3N2) virus epidemic occurred in China in 2017 and the causative strain failed to bind red blood cells (RBCs), which may affect receptor binding and antibody recognition. The objective of this study was to analyze the genetic characteristics and glycosylation changes of this novel H3N2 strain. We directly sequenced the hemagglutinin (HA) genes of H3N2 clinical specimens collected from patients with acute respiratory tract infection during 2017 in Guangdong, China. We aligned these sequences wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Recombinant HA proteins engineered to possess I160 (2a2 and 2a1 –glycan) also migrated with a lower molecular weight compared to HAs with T160 (2a1 and 2a2 +glycan) ( Figure S1 B), consistent with a loss of a glycosylation site with the T160I substitution. Influenza virus entry into human cells is mediated by HA binding to α2,6-linked sialoglycans ( Thompson and Paulson, 2021 ), and previous studies have demonstrated that the 158–160 HA glycosylation site impacts HA sialic acid binding specificity ( Zeng et al., 2020 ). To determine if the 2a2 H3N2 HA has altered receptor specificity, we measured HA binding to a panel of α2,3- and α2,6-linked sialoside glycans ( Figures 1 C and Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant HA proteins engineered to possess I160 (2a2 and 2a1 –glycan) also migrated with a lower molecular weight compared to HAs with T160 (2a1 and 2a2 +glycan) ( Figure S1 B), consistent with a loss of a glycosylation site with the T160I substitution. Influenza virus entry into human cells is mediated by HA binding to α2,6-linked sialoglycans ( Thompson and Paulson, 2021 ), and previous studies have demonstrated that the 158–160 HA glycosylation site impacts HA sialic acid binding specificity ( Zeng et al., 2020 ). To determine if the 2a2 H3N2 HA has altered receptor specificity, we measured HA binding to a panel of α2,3- and α2,6-linked sialoside glycans ( Figures 1 C and Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Viruses from clade 3c.3a typically lack this glycosylation at site 160, exposing antigenic epitopes which may be covered up in 3c.2a viruses that have this glycosylation ( 5 , 66 ). The glycosylation at site 160 impacts the HA sialic acid binding specificity, which plays a role in the HA protein binding to host cell receptors ( 65 , 67 ). NG2 and Kan/17 HA proteins also differ by 11 amino acids and 4 of those residues reside in antigenic sites of the H3 HA protein.…”
Section: Discussionmentioning
confidence: 99%
“…1 VLPs were harvested at 72 h post infection of the High Five cells. 2 Hemagglutination assay is not suitable for quantifying HA protein of recent influenza H3N2 viruses [21][22][23]. 3 HA concentration was not determined because samples were aggregated.…”
Section: Pilot Evaluation Of Vlps Stabilitymentioning
confidence: 99%
“… 1 Estimated HA yield (mg/L) was based on the HA content (µg/mL) and volume (1.2 mL) after purification using 40 mL working volume and calculated by converting working volume from 40 mL to one liter. 2 Hemagglutination assay is not suitable for quantifying HA protein of recent influenza H3N2 viruses [ 21 , 22 , 23 ]. …”
Section: Figurementioning
confidence: 99%